Environmental literacy among undergraduates of environmental programs at public research universities in Selangor, Malaysia - Jeganathan, Cheryl Stephen (2012)
Evaluating environmental literacy has been one of the mode by which the extend where the understanding between the nature of interdependence between the natural system and the human social system could be established. While there are many universities that have begun to evaluate their undergraduates, the environmental literacy of undergraduates in Malaysia, have yet to be assessed. The objective of this study is to determine the environmental literacy of the environmental undergraduates at public research universities in Selangor. In this study, a descriptive research method was used. The set of questionnaires were constructed in different sections, Environmental Attitude, Environmental Behaviour and Environmental Knowledge. Data was collected using a self administered questionnaire to identify the level of environmental literacy among 418 undergraduates enrolled in environmental programs at Universiti Putra Malaysia and Universiti Kebangsaan Malaysia. All the respondents targeted responded to the study. The result of the study shows that the Environmental Literacy dispositions of the undergraduates were generally found to be at the moderate level, with a mean of 3.47 based on a five-point scale. When comparison was done using the contributive variable, undergraduates were found to be high in terms of their environmental behavior (Mean=3.81) and environmental attitude (Mean=3.68) and moderate level of environmental knowledge (Mean=2.93). The dispositions of the undergraduates are similar regardless of the different environmental program taken in public research universities in Selangor or in the nature of their gender. Undergraduates in Year 2 show increased level of environmental knowledge compared to Year 1. However, undergraduates from Year 3 and above do not show significant increase in this field compared with the undergraduates in Year 2. The results were similar to the previous researches, which was presented in the discussion section. It can be concluded that the environmental literacy of the undergraduates is in the moderate level, mainly contributed by moderate level of environmental knowledge, which needs improvement. The Environmental Literacy of the undergraduates is not influenced by the different environmental programs or by gender. Recommendations were discussed at the final chapter on enhancing in further study on research of environmental literacy.